Isolation, identification and in vitro screening of grapevine yeasts for the control of black aspergilli on grapes - Pantelides, Iakovos; Christou, Ourania; Tsolakidou, Maria Dimitra; Tsaltas, Dimitrios; Ioannou, Nicolas (My University, 2015)
Antagonistic yeasts were isolated from the surface of grape berries cv. "Cabernet sauvignon" and "Maratheftiko" from six vineyards in Cyprus and identified at species level using molecular methods. The identification revealed that the yeast isolates belonged to seven taxonomically distinct groups: Aureobasidium pullulans, Cryptococcus magnus, Hanseniaspora uvarum, Candida zeylanoides, Candida sake, Rhodotorula mucilaginosa and Pseudozyma aphidis. A total of 55 yeast isolates were evaluated in a preliminary screening test on agar to select isolates exhibiting inhibition against an ochratoxigenic strain of Aspergillus tubingensis. Thirty-three yeast isolates were selected for their antisporulant activity on A. tubingensis and their ability to reduce the growth of fungal mycelium. These isolates were assayed by a detached berry test for their ability to inhibit infection by the ochratoxigenic strain of A. tubingensis. Twenty-eight yeast isolates belonging to three species, namely 25 isolates of A. pullulans, 2 isolates of C. magnus and 1 isolate of C. sake, reduced the A. tubingensis colonization of grape berries. The highest antagonistic activity was shown by the A. pullulans isolates, with biocontrol efficacies ranging between 17.1% and 95.7%. The results of this study suggest that antagonist yeasts potentially effective for biological control of A. tubingensis on grape can be found among the microbiota associated with grape berries in Cyprus vineyards.
Keywords: Aspergillus section Nigri; Aureobasidium pullulans; Biocontrol; Epiphytic yeast; Grapes; Ochratoxin A